Implementation of the SMART Method in a Decision Support System for Scholarship Selection Using Real Data - Elida Tuti Siregar; Nurhayati Nurhayati; Ria Eka Sari; Fitri Pranita Nasution; Nur Anzelina Harahap (Universitas Methodist Indonesia, 2026)
The process of selecting scholarship recipients at SMK MEDAN still faces issues of subjectivity and inefficiency due to manual procedures. This study aims to develop a scholarship decision support system based on the SMART (Simple Multi Attribute Rating Technique) method within the Decision Support System (DSS) framework to enhance objectivity and transparency in decision-making. This research employs a quantitative approach within an applied research framework using real student data based on criteria such as academic achievement, parents’ income, number of dependents, and attendance. The results indicate that the SMART method effectively generates a consistent multi-criteria ranking model, where the top candidate achieves a preference score of 0.833, equivalent to an 83.3% eligibility level. The developed system improves decision quality through more objective and efficient educational decision optimization. The main contribution lies in integrating SMART with real data into an application-based system, offering a more transparent and practical approach compared to conventional methods.